A new coil structure for increasing power transfer and misalignment tolerance of wireless electric vehicle charging system / Amran Hossain - Amran, Hossain (2022)
Most of the Inductive power transfer (IPT) systems have only one energy transmission path, which is difficult to be used for high power applications. So multiple coils i.e, more than one coil for transmitter and receiver are considered. However, for such configuration, the efficiency decreases due to the cross-couplings among the same side coils. In most of the existing multiple coil topologies, decoupling coils are used to mitigate the same side couplings. Typically these coils are either placed outside the main coils or concentric with the main coils. In both cases, these decoupling coils do not take part in power transmission while at the same time presenting negative effects on the system performance. In this work, a new IPT system with dual transmitters and dual receivers with integrated decoupling coils is introduced. The main feature of the design, the decoupling coils not only mitigate the mutual inductances of the same side coils, in addition, but the coils are also involved in the power transmission. Another important characteristic of the proposed IPT is the ability to maintain good performance when the main coils are misaligned in both X and Y directions. A finite element analysis (FEA) tool ANSYS MAXWELL was used to investigate the proposed magnetic coupler. A scaled-down experimental setup is provided to verify the feasibility of the proposed structure. The maximum dc-dc efficiency for this system was achieved at 93.14% while delivering 700 W to the load with a 200mm air gap. The efficiency is 91.8 % at 50 % misalignment of the coil length (200mm) in the X direction and the efficiency is 82.06% at 150mm misalignment in the Y direction. Besides, Zero Voltage Switching (ZVS) was also achieved, which validates that the proposed system can be an effective solution for the current drawbacks of the multiple receivers and transmitters. The proposed method is compared to other established coil IPT from the literature. It is found that the proposed system has better performance in terms of efficiency and misalignment than these of the others.